Fabrication of Antimicrobial Multilayered Nanofibrous Scaffolds-Loaded Drug via Electrospinning for Biomedical Application - Liu, Qi; Jia, Hengmin; Ouyang, Wenchong; Mu, Yan; Wu, Zhengwei (Frontiers in Bioengineering and Biotechnology, 2021)
Nanofibers prepared by bio-based materials are widely used in the field of biomedicine, owing to outstanding biocompatibility, biodegradable characters and excellent mechanical behavior. Herein, we fabricated multilayered nanofibrous scaffolds in order to improve the performance of drug delivery. The developed composite layer-by-layer scaffolds incorporated by hydrophobic poly (l-lactic acid) (PLA): polycaprolactone (PCL) and hydrophilic poly (vinyl alcohol) (PVA) nanofibers via multilayer electrospinning. Morphological and structural characteristics measured by scanning electron microscopy (SEM) confirmed uniform and beadless nanofibers were formed. The differences of contact angles and Fourier transform infrared spectrum (FTIR) between single-layered PVA nanofibers and multilayered scaffolds verified the existence of PLA:PCL surface. In vitro biodegradable analysis depicted multilayered scaffolds had good biodegradability and potential for medical application. Due to the model drug incorporation, scaffolds exhibited good antibacterial activity against Escherichia coli and Staphylococcus aureus by zone of inhibition test. These results revealed that the multilayered scaffolds were proved to be desirable antibacterial materials as biomedical application.